Ruptured Hemorrhagic Ovarian Cyst Presenting as an Incarcerated Inguinal Hernia in an Adult Female: A Rare Clinical Scenario of a Common Surgical Emergency. (18th April 2013) - Jategaonkar, Priyadarshan Anand; Yadav, Sudeep Pradeep
Abstract : Embryoanatomical peculiarities are responsible for low occurrence of inguinal hernias in females. Amongst them, ovarian hernias are rarer. They are commonly noticed in children. An attending surgeon commonly faces diagnostic and operative dilemmas in managing these overtly "simple-looking" clinical scenarios. Although ovarian cysts are one of the common contents of the sac, we report a case of adult incarcerated ovarian hernia who presented with a ruptured hemorrhagic ovarian cyst. This differential should be kept in mind while treating an adult female with painful inguinal swelling. As far our knowledge goes, such case with ruptured ovarian cyst presenting as an incarcerated hernia in an emergency scenario has not been reported as yet.